Brand dynasty: managing charismatic legitimacy over time. Issue 3 (12th February 2023) - Arnould, Eric; Dion, Delphine
ABSTRACT: Drawing upon extensive research in luxury, we investigate how firms manage to sustain charismatic legitimacy over a succession of charismatic heirs. We question the presumption that charismatic legitimacy is personal and transitory. Instead, we show that management can deal with the inherent human limitations of charismatic legitimacy by forming a brand dynasty. We define a brand dynasty as a brand in which a series of persons (brand heirs) embody the brand persona that is defined by reference to a brand founder. Our analysis identifies three general managerial practices that together transfer and when repeated sustain brand charismatic legitimacy.